Better-surviving barn swallow mothers produce more and better-surviving sons. (1st May 2016) - Romano, Andrea; Costanzo, Alessandra; Caprioli, Manuela; Parolini, Marco; Ambrosini, Roberto; Rubolini, Diego; Saino, Nicola
Abstract: Sex allocation theory predicts that parents are selected to bias their progeny sex ratio (SR) toward the sex that will benefit the most from parental quality. Because parental quality may differentially affect survival of sons and daughters, a pivotal test of the adaptive value of SR adjustment is whether parents overproduce offspring of the sex that accrues larger fitness advantages from high parental quality. However, this crucial test of the long-term fitness consequences of sex allocation decisions has seldom been performed. In this study of the barn swallow ( Hirundo rustica ), we showed a positive correlation between the proportion of sons and maternal annual survival. We then experimentally demonstrated that this association did not depend on the differential costs of rearing offspring of either sex. Finally, we showed that maternal lifespan positively predicted lifespan of sons but not of daughters. Because in barn swallows lifespan is a strong determinant of lifetime reproductive success, the results suggest that mothers overproduce offspring of the sex that benefits the most from maternal quality. Hence, irrespective of mechanisms causing the SR bias and mother–son covariation in lifespan, we provide strong evidence that sex allocation decisions of mothers can highly impact on their lifetime fitness.